2021
DOI: 10.1371/journal.pone.0258430
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative assessment of various supplementary diets on commercial honey bee (Apis mellifera) health and colony performance

Abstract: A healthy honey bee stock is critical to the beekeeping industry and the sustainability of the ecosystem. The quality of the supplemental diet influences the development and strength of the colony, especially during the pollen dearth period in the surrounding environment. However, the extent to which pollen substitute protein feeding affects honey bee colony parameters is not fully known. We conducted this study to test the influence of various supplemental diets on foraging effort, pollen load, capped brood a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
1
11
0
1
Order By: Relevance
“…Similar findings have been reported in the sealed brood area in previous literature ( Sihag and Gupta, 2011 , Lamontagne-Drolet et al, 2019 , Ahmad et al, 2021b ); various pollen substitutes increased the worker brood area. However, our results are inconsistent with the findings of Ali (2011), who reported that the worker brood area was 2813.13 cm 2 /colony, 1730.94, and 1867 cm 2 /colony in different groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar findings have been reported in the sealed brood area in previous literature ( Sihag and Gupta, 2011 , Lamontagne-Drolet et al, 2019 , Ahmad et al, 2021b ); various pollen substitutes increased the worker brood area. However, our results are inconsistent with the findings of Ali (2011), who reported that the worker brood area was 2813.13 cm 2 /colony, 1730.94, and 1867 cm 2 /colony in different groups.…”
Section: Discussionsupporting
confidence: 91%
“…Honey bee colonies are fed on commercially available pollen substitute diets when the natural pollen resources are scarce. Artificial pollen substitutes may affect bee physiology in addition to their primary nutritional role ( Al-Ghamdi et al, 2011 , Ahmad et al, 2021b ). For instance, sugar syrup is the most often used artificial diet for honey bees.…”
Section: Introductionmentioning
confidence: 99%
“…In cases where the flora is insufficient, the quality of supplementary feeding affects the development and strength of the colony [50]. In the study conducted by Ahmed et al (2021), it was determined that feeding with pollen substituted diet increased the number of bee frames and brood area, while it was determined that the consumption amount was higher compared with the control [50]. Contrary to our findings, Mortensen et al (2019) reported that there is no change depending on the presence and source of protein [51].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a significant improvement in the antioxidant system was reported in bee colonies given a supplemental diet for 18 weeks compared with other treatments and controls [ 49 ]. In cases where the flora is insufficient, the quality of supplementary feeding affects the development and strength of the colony [ 50 ]. In the study conducted by Ahmed et al (2021), it was determined that feeding with pollen substituted diet increased the number of bee frames and brood area, while it was determined that the consumption amount was higher compared with the control [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Часто пасічники у певні періоди протягом активного сезону здійснюють підгодівлю бджіл різними стимулюючими добавками (Gemeda, 2014;Shumkova et al, 2017;Разанова & Голубенко, 2018; Barroso-Arévalo et al, 2019). У бджільництві на даний час застосовують значну кількість стимуляторів, які позитивно впливають на обмін речовин, покращуючи використання корму, прискорюють ріст бджолиних сімей (Tawfik et al, 2020; Разанов та ін., 2020; Saranchuk et al, 2021), сприяють поліпшенню результатів зимівлі (Guler et al, 2018), збільшенню прийому личинок на маточне виховання (Gençer et al, 2000) та підвищенню продуктивності бджолиних сімей (Ahmad et al, 2021;Разанова, 2021;Ullah et al, 2022).…”
unclassified